Chemically graded Fe–Al/steel samples fabricated by laser metal deposition. (30th January 2017) - Lotfian, Saeid; Rolink, Gesa; Weisheit, Andreas; Palm, Martin
ABSTRACT: By laser metal deposition (LMD) samples from Fe–28Al (at.%) have been built on iron and various steels. Chemically graded iron aluminium and Fe–28Al/steel samples were fabricated with intended concentration gradients by controlling the feed rates of the powders. All samples were subsequently heat treated at 700 °C for 1000 h to study possible reactions between Fe–28Al and the steels and the long-term stability of the composition gradients. Microstructures were characterized by scanning electron microscopy (SEM) and concentration profiles along the building direction were analysed by energy- and wavelength-dispersive spectrometry (EDS, WDS).